Maternal near miss review: a brief appraisal - Marwah, Sheeba; Sharma, Manjula (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Recuperation of maternal health is mandatory for realms signatory to millennium declaration, as MDG 5A aims at reduction in maternal mortality ratio by three quarters between 1990 and 2015. MM is frequently described as “Just the Tip of The Iceberg” with a vast base of maternal morbidity that still remains largely undescribed. Hence, the concept of maternal near miss (MNM) or severe acute maternal Morbidity (SAMM) was instituted in maternal health care to complement information acquired from MDR. Here we present a succinct review to enlighten and update the readers about the concept of maternal near miss and its advantage in providing the modern-day obstetricians and the administrators an edge over maternal mortality in gauging the quality of health care delivered at each facility. This would thus be instrumental in helping them formulating policies to enhance the health care services at each level across the nation.